2021
DOI: 10.21142/des-1301-2021-0012
|View full text |Cite
|
Sign up to set email alerts
|

Emprendimiento y resiliencia: caso de las bodegas de barrio en el Perú durante la pandemia de covid-19

Abstract: Las bodegas de barrio en el Perú representan uno de los canales de venta más importantes en los hogares pe- ruanos y tienen una participación mayor al 70% en las ventas minoristas. Con una pirámide socioeconómica de la población en la que predominan los sectores medio, bajo y muy bajo con una capacidad de compra limitada, las bo- degas tienen un arraigo muy fuerte en los barrios del Perú. Además de destacar en el abastecimiento de productos de primera necesidad, también tienen un rol social y antropo- lógico e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…In terms of the scientific evidence of entrepreneurship in South America during the COVID-19 pandemic, this systematic review revealed 15 records [111][112][113][114][115][116][117][118][119][121][122][123][124][125]. There were scientific articles that were written in one of three languages: Spanish (5 cases), Portuguese (3 cases), and English (4 cases); but there were also articles with two versions available: in Portuguese and English (3 cases).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the scientific evidence of entrepreneurship in South America during the COVID-19 pandemic, this systematic review revealed 15 records [111][112][113][114][115][116][117][118][119][121][122][123][124][125]. There were scientific articles that were written in one of three languages: Spanish (5 cases), Portuguese (3 cases), and English (4 cases); but there were also articles with two versions available: in Portuguese and English (3 cases).…”
Section: Discussionmentioning
confidence: 99%
“…For the authors Valencia & Duche (2019) there is a high correlation between management innovation and competitive success in companies, this should drive innovation in organizations in either processes, marketing, product or technological position to be accepted by consumers. Therefore, in the face of the pandemic, managers must seek ways to change strategies totally or partially (with respect to a certain area) to face the changes presented in the environment (Acuña, 2021;García et al, 2021) and thus improve business competitiveness. Given the current situation, the Peruvian state cannot be oblivious to the problem, it has to present supports to promote business innovation such as the Innóvate Perú program, which promotes the social, economic and health reactivation of the country and is aimed at both SMEs and large companies (Ministerio de la Producción, 2022).…”
Section: Entrepreneurial Innovation In Smes In Metropolitan Lima As A...mentioning
confidence: 99%
“…The rates of unemployment and lack of job opportunities in Peru, in addition to the rapid scientific and technological advancement, they forge the need for a priori of a sustained growth of the economy and to do so requires you to professional profiles that have the characteristics of entrepreneurs (Acuña, 2021).…”
Section: Entrepreneurship In the Perumentioning
confidence: 99%